Myeloid differentiation factor 2 inhibitor and N-acetyl cysteine synergistically reduced left ventricular dysfunction in rats with cardiac ischemia/reperfusion injury. (3rd October 2022) - Apaijai, N; Vongsfak, J; Singhanat, K; Arunsak, B; Samneong, N; Maneechote, C; Chunchai, T; Chattipakorn, S; Chattipakorn, N
Abstract: Background: Myeloid differentiation factor 2 inhibitor (MD2i) is a novel anti-inflammatory agent that exerts favorable outcomes in various diseases including cardiac ischemia/reperfusion (I/R) injury. However, whether a potent antioxidant N-acetyl cysteine (NAC) can augment the beneficial effects of MD2i in rats with cardiac I/R injury have never been investigated. Purpose: We tested the hypothesis that NAC increases the beneficial effects of MD2i against cardiac I/R injury in rats. Methods: Rats were divided into either a sham (n=6) or cardiac I/R group (n=72). Rats in the I/R group received one of the following 6 treatments (n=12 each) at the onset of reperfusion: vehicle, MD2i at 20 and 40 mg/kg, NAC at 75 and 150 mg/kg, and combined MD2i 20 mg/kg with NAC 150 mg/kg. Left ventricular (LV) function, infarct size, arrhythmia score, and cardiac mitochondrial function and dynamics were determined. Results: Myocardial infarction, LV dysfunction, and cardiac arrhythmias were observed in rats with cardiac I/R injury, along with mitochondrial dysfunction (Fig. 1). Treatment with MD2i at either 20 or 40 mg/kg effectively reduced LV dysfunction but failed to reduce the infarct size (Fig. 1). NAC at 150 mg/kg, but not at 75 mg/kg, significantly decreased both LV dysfunction and infarct size following cardiac I/R injury (Fig. 1). However, combined treatment exerted even greater efficacy in reducing cardiac I/R injury than monotherapy, through a greater reduction of cardiac mitochondrial dysfunction and mitochondrial fission (Fig. 1). However, no benefit on reducing the arrhythmia score in all groups. Conclusion: Combined MD2i and NAC treatment exerted a superior cardioprotective effect against cardiac I/R injury than either monotherapy regimen via an improved cardiac mitochondrial function. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): 1. NSTDA Research Chair Grant from the National Science and Technology Development Agency Thailand2. National Research Council of Thailand